CHANGES OF INTERCELLULAR COOPERATION IN PERIPHERAL BLOOD IN TREATED PATIENTS WITH CARDIOLOGIC DISEASES - L. N. Korichkina; V. S. Volkov (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study changes of intercellular cooperation in peripheral blood induced by treatment in patients with arterial hypertension (HT), ischemic heart disease (IHD) and chronic heart failure (CHF).Material and methods. 610 patients were involved into the study, including 250 patients with HT of stages I-III (50 untreated patients), 150 patients with IHD and 210 patients with CHF of stages I-III. All patients were treated except 50 hypertensive ones. 80 healthy patients (40 men, 40 women) were included into control group. Blood smears of patients were evaluated (Romanovsky's stain). A number of leukocyte, autorosettes and autorosettes with erythrocyte lysis was calculated. The cellular association consisting of a neutrophil, monocyte or eosinocyte with 3 or more erythrocytes skintight to their surface defined as autorosettes. Erythrocytes number and hemoglobin level determined in peripheral blood.Results. Single autorosettes in peripheral blood were observed in patients of control group and in untreated patients with HT. Treated patients with HT, IHD and CHF had increased number of autorossets and autorosettes with erythrocytes lysis. This phenomenon resulted in reduction of erythrocytes number and hemoglobin level in peripheral blood.Conclusion. Treated patients with cardiologic diseases had changes in intercellular cooperation. It should be considered at intensive and long term therapy.